A Simplified high resolution MODIS Aerosol Retrieval Algorithm (SARA) for use over mixed surfaces - Bilal, Muhammad; Nichol, Janet E.; Bleiweiss, Max P.; Dubois, David (Remote sensing of environment, 2013)
Aerosol Optical Depth (AOD) is a measure of the columnar atmospheric aerosol content. Satellite remote sensing has been used to retrieve AOD over land and ocean at spatial resolutions of several to several tens of km. In most cases, a Radiative Transfer Model (RTM) is used to construct a look-up table (LUT) to act as a map between measurements and physical quantities. In the current study, MODerate resolution Imaging Spectroradiometer (MODIS) measurements were used to develop a Simplified Aerosol Retrieval Algorithm (SARA) for use over Hong Kong at high (500m) spatial resolution, without using a LUT. Instead, RTM calculations were applied directly to the MODIS data, with the aerosol properties derived from a local urban Aerosol Robotic Network (AERONET) station at the Hong Kong Polytechnic University, and surface reflectance from the MOD09GA level-2 daily surface reflectance product. For validation, the SARA AOD at 500m, along with the operational MODIS aerosol product (MOD04 C005) at 10km spatial resolution, was compared with data from a ground-based Microtops II sun photometer at the Hong Kong International Airport, a Sky-radiometer at the City University of Hong Kong, and an AERONET station at Hong Kong Hok Tsui. The 500m AOD retrieved from the SARA showed a high consistency with ground-based AOD measurements, with average correlation coefficient ~0.964, root mean square error (RMSE) ~0.077, and mean absolute error (MAE) ~0.065. The SARA AOD showed a good agreement with MOD04 C005 AOD over both urban and rural areas of Hong Kong, with average correlation coefficient ~0.917, RMSE ~0.087, and MAE ~0.072. The results demonstrate that our simplified AOD algorithm is better able to represent aerosol conditions over Hong Kong than the MOD04 C005 standard product as well as other higher resolution algorithms which have been tested over Hong Kong. •A simplified, high resolution Aerosol Retrieval Algorithm (SARA) is presented.•The SARA algorithm does not require a look–up–table (LUT) in the computation.•The SARA algorithm works well over both dark rural, and bright urban surfaces.•SARA achieves better accuracy than MOD04 C005 AOD and has superior spatial detail.•C005 AOD does not work well over bright airport surfaces, and for high AOD levels.